2018
DOI: 10.1111/soin.12262
|View full text |Cite
|
Sign up to set email alerts
|

Socioeconomic Resource Environments in Biological and Alternative Family Care and Children's Cognitive Performance*

Abstract: We examined social and economic resources in the environments of children involved with child protective services and their associations with children's cognitive performance. We used a national dataset of child protection investigations (children aged 6–16 at Wave 1). Using latent class analysis, we constructed profiles of the financial resources, parental education and employment, and family structure and size. We then examined within‐ and across‐time associations between resource environment profiles and ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 86 publications
(131 reference statements)
0
3
0
Order By: Relevance
“…Yet, understanding children’s experiences within their foster homes is critical to making real progress on issues of placement instability and negative well‐being outcomes. The quality of foster homes has been the subject of a limited body of research, which has found wide variability in resources, parenting behaviors, and outcomes (Berrick, 1997; Crum, 2010; Font & Potter, 2019; Simms & Horwitz, 1996). Standardized assessments such as the Home Observation for the Measurement of the Environment (HOME) Inventory (Caldwell & Bradley, 2018) or the Structured Analysis Family Evaluation (SAFE: Consortium SAFE, 2011), have been used by some child welfare agencies in home studies for prospective foster or adoptive families (Selwyn, 2011).…”
Section: Opportunities For Foster Care Reform Through Policymentioning
confidence: 99%
“…Yet, understanding children’s experiences within their foster homes is critical to making real progress on issues of placement instability and negative well‐being outcomes. The quality of foster homes has been the subject of a limited body of research, which has found wide variability in resources, parenting behaviors, and outcomes (Berrick, 1997; Crum, 2010; Font & Potter, 2019; Simms & Horwitz, 1996). Standardized assessments such as the Home Observation for the Measurement of the Environment (HOME) Inventory (Caldwell & Bradley, 2018) or the Structured Analysis Family Evaluation (SAFE: Consortium SAFE, 2011), have been used by some child welfare agencies in home studies for prospective foster or adoptive families (Selwyn, 2011).…”
Section: Opportunities For Foster Care Reform Through Policymentioning
confidence: 99%
“…Many studies linking economic supports to child maltreatment were either aggregate (state-level) analyses from which it is challenging to draw conclusions about the specific nature of changes in risk of harm or focused on economic supports that involve at least one parent in the labor force, such as the earned income tax credit (Berger et al, 2017), child support (Cancian et al, 2013), or minimum wage (Raissian & Bullinger, 2017). Because factors like substance abuse, unmanaged mental illness, and violence are not conducive to stable employment (Ringbom et al, 2022; Sherba et al, 2018) and many parents investigated by CPS do not have stable or full-time employment (Dolan et al, 2011; Font & Potter, 2019), it is questionable whether such policies, in isolation, will reduce neglect in those family contexts. Further research is needed to ascertain the mechanisms through which packaging economic supports with health- and behavior-focused interventions may reduce conditions that lead to CPS involvement.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, children in OOHC disproportionately experience the conditions of poverty that can lead to academic difficulties and social and behavior problems (Huston & Bentley, 2010;Jensen, 2009). For example, Font and Potter's (2019) study indicates that the reading and math scores of children involved in CPS are negatively affected by the placement of children in severely disadvantaged environments.…”
Section: Theoretical Frameworkmentioning
confidence: 99%